Respostas
respondido por:
23
y = - x² + 2x
0 = - x² + 2x
- x² + 2x = 0
x . (- x + 2) = 0
x = 0
- x + 2 = 0
- x = - 2 . (- 1)
x = 2
Resp.: O maior valor que y pode assumir é 2.
0 = - x² + 2x
- x² + 2x = 0
x . (- x + 2) = 0
x = 0
- x + 2 = 0
- x = - 2 . (- 1)
x = 2
Resp.: O maior valor que y pode assumir é 2.
respondido por:
8
y= -x² + 2*x
y = -(x*(x - 2))
x * (x - 2) = 0
uma raiz é x => x = 0
a outra é:
x - 2 = 0
x = 2
y = -(x*(x - 2))
x * (x - 2) = 0
uma raiz é x => x = 0
a outra é:
x - 2 = 0
x = 2
Helvio:
de nada.
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás